Representations of Women in Nineteenth-Century Brazilian Literature - Faria, João Roberto Gomes de (ABEI Journal, 2006)
This essay discusses the representation of women in nineteenth-centuryBrazilian literature. Portraits of rich women, wives, lovers, widows and “oldmaids” can be seen in the literature produced in that period, but every one of them is drawn by men.